Spanish organisations : inter-departmental correspondence (copy) - McDonald, Florence
010-0140-001 F. McDonald Mr. Woodcock. Secretary's 12th August, 1936. Spanish Organisations. Would you get someone in your Department to look up the analysis of the Spanish elections held last February. It has been published somewhere. Sir Walter would also like a card prepared giving the names of the central Labour organisations in Spain. The "Times" published a list of the Barcelona organisations giving the initials generally used. It is the Barcelona and Madrid organisations which he really wants. 292/946/10/153